Transesterification of Jatropha and Karanja oils by using waste egg shell derived calcium based mixed metal oxides. (15th May 2015) - Joshi, Girdhar; Rawat, Devendra S.; Lamba, Bhawna Y.; Bisht, Kamal K.; Kumar, Pankaj; Kumar, Nayan; Kumar, Sanjay
Graphical abstract: Highlights: Waste chicken eggshell derived CaO(cesp) based mixed metal oxides were prepared. Transesterification of high free fatty acid containing non-edible oils were achieved using prepared catalysts. CaO(cesp) based mixed metal oxides have shown better activity in comparison to neat CaO(cesp). Best Conversions were achieved with ZnO–CaO(cesp). Catalyst has shown good reusability up to 4 cycles without significant loss in its activity. Abstract: Solid base heterogeneous catalysts are one of the promising materials for the transesterification of vegetable oils because these catalysts are generally more reactive than solid acid catalysts which require very severe operating conditions. Calcium oxide has shown good catalytic activity due to its high basicity which is required for transesterification of triacylglycerides (TAGs). In the present study, the transesterification of non-edible, high free fatty acid containing Jatropha and Karanja oils was studied by using waste chicken egg shell derived calcium (i.e. CaO(cesp)) based mixed metal oxides (M-CaO; M = ZnO, MnO2, Fe2 O3 and Al2 O3 ) as heterogeneous catalyst. A comparison was also made on the catalytic performance of these prepared catalysts. The catalyst characterizations were done by XRD, SEM, TGA, FT-IR and BET techniques. The effectiveness of the catalysts was highly influenced by the calcination temperature. ZnO–CaO(cesp) catalyst was found to be the most efficient catalyst among all. The maximum conversion for the transesterification of Jatropha and Karanja oils were achieved using 5 wt% catalyst, 65 °C temperature and 12:1 methanol/oil ratio. The catalyst could be re-used effectively during four cycles. Use of the CaO(cesp) based mixed oxides made the process more environmental benign and economical. The biodiesel prepared has shown good fuel characteristics as per EN, ASTM and IS standards.